Quem somos nós?: ciência e mídia fabricando subjetividades - FREITAS, Lilliane Miranda (Universidade Federal do Pará, 2012)
This research had as objective investigating the process of constructing identities at the intersection of media and scientific discourse. To this end elected as a source of the empirical data analyzed here reports from Superinteressante magazine. Among the editions of 2008 the magazine was selected in those reports that the biological discourse was the central argument to the production of subjectivities. Two were the main issues that guided the investigative journey: “Which identities are manufactured from the speech carried out by biological science magazines? “What is the social productivity of these speeches?” I analyzed the problem with the theoretical tools of thought of Michel Foucault some theoretical and the Cultural Studies and Cultural Studies of Science, in order to consider the connection between power / knowledge of production of subjectivities through cultural pedagogy and media to discuss the nature contingent and the power relationships present in biological discourses. In this study the media is regarded as a cultural pedagogy that teaches us ways of being and seeing, regulates conduct, naturalize meanings, and it is involved actively in the formation of social identities. Considering those ideas, discuss the constructed nature of subjectivity, to think that the ways we live our subjectivities and hold subjects’ positions are historically and culturally conditioned. Based on these theoretical assumptions, the empirical material grouped into six themes core that answer the research questions. They are: 1) Moral Subject, in which morality appears as a characteristic innate and universal to the human 2) Instinctive Subject, defining certain social behaviors as instinctive fruits of a supposed human nature; 3) DNAtidade in which genetic discourse appears as a determining factor in predicting what they are and how people will live; 4) Psi Subject discusses how the subjectivities are managed and administered by individuals psychologization 5) Gendered Subject in which the attributes of masculinity and femininity appear naturally and essentialized in relation to gender and 6) Aesthetic Subject which are defined in certain ways and of course the best body. The analysis of all identities produce in the speech we take calls on biological/scientific and other discourses as social constructions, historical and cultural, an important discussion for Education Sciences for questioning those truths that become hegemonic to teach science. To highlight the discursive construction of identity, the strategies of formal regulation to experience our subjectivities, this allows us to participate in this process of construction and therefore includes the possibility positions of resistance against hegemonic discourses, not face social identities as monolithic and fixed. This is an important issue to be discussed in education in order to generate processes of social transformations, since, as we saw and the way we are seen determines in part how we treat and are treated in social relations.